"YFlag" – A Single‐base Extension Primer Based Method for Gender Determination. Issue 1 (30th October 2014) - Allwood, Julia S.; Harbison, Sally Ann
Abstract Assigning the gender of a DNA contributor in forensic analysis is typically achieved using the amelogenin test. Occasionally, this test produces false‐positive results due to deletions occurring on the Y chromosome. Here, a four‐marker "YFlag" method is presented to infer gender using single‐base extension primers to flag the presence (or absence) of Y‐chromosome DNA within a sample to supplement forensic STR profiling. This method offers built‐in redundancy, with a single marker being sufficient to detect the presence of male DNA. In a study using 30 male and 30 female individuals, detection of male DNA was achieved with c. 0.03 ng of male DNA. All four markers were present in male/female mixture samples despite the presence of excessive female DNA. In summary, the YFlag system offers a method that is reproducible, specific, and sensitive, making it suitable for forensic use to detect male DNA.